2009
DOI: 10.1080/87565640903265129
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Emotion Processing in Typically Developing Children and Children of Diabetic Mothers

Abstract: To examine the neurocognitive sequelae of children born to diabetic mothers (CDMs), event-related potentials (ERPs) in response to three facial expressions (happy, fear, anger) were collected from 42 children (18 CDMs, 24 controls), aged 36 and/or 48 months. A linear mixed models approach was used to model individual variation in amplitude and latency. As infants, CDMs in the present study displayed subtle impairments in attention and memory processing, including face recognition, as indexed by ERPs. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
(82 reference statements)
2
5
0
Order By: Relevance
“…The suboptimal metabolic control during GD has been suggested to cause dysfunctions at the cortical level in the brain; this hypothesis is partly supported by previous studies carried out in humans and animals. [ 32 36 ] Our results suggest a mechanism that includes impaired neuronal function, since cVEPs are considered a proxy for neuron myelination (latencies) and visual acuity (amplitudes),[ 37 , 38 ] and are in agreement with studies reported by Brinciotti et al[ 18 , 39 ]…”
Section: Discussionsupporting
confidence: 90%
“…The suboptimal metabolic control during GD has been suggested to cause dysfunctions at the cortical level in the brain; this hypothesis is partly supported by previous studies carried out in humans and animals. [ 32 36 ] Our results suggest a mechanism that includes impaired neuronal function, since cVEPs are considered a proxy for neuron myelination (latencies) and visual acuity (amplitudes),[ 37 , 38 ] and are in agreement with studies reported by Brinciotti et al[ 18 , 39 ]…”
Section: Discussionsupporting
confidence: 90%
“…5 In relation to the CNS, previous studies have noted that infants of diabetic mothers have impairments in habituation to stimulation and emotional processing. 6,7 In a study by Gonzalez-Gonzalez et al 6 on fetuses with maternal pregestational diabetes, it was observed that the fetuses in the diabetic group had difficulty in habituating to vibroacoustic stimulation and their results were similar to an earlier study by Doherty et al 8 Additionally, they also noted that high levels of maternal glycated hemoglobin (HbA 1c ) in any of the trimesters of pregnancy had significantly negative correlation with infant recordings of habituation ability. It has also been reported that neonates of mothers with type 1 diabetes showed a higher percentage of immature and disorganized EEG patterns and excessive transient sleep waves, which are associated with brain injury and cognitive deficits.…”
Section: Introductionsupporting
confidence: 55%
“…A similar and likely analogous waveform was modulated by facial affect in a sample of institutionalized Romanian children in this age range (Parker et al, 2005). Further, a similar component observed in 3- and 4-year-old children of diabetic mothers, identified as the positive-going aspect of the N1-P2 complex, was found to vary in latency across affective facial expressions (Cordon, Georgieff, & Nelson, 2009).…”
mentioning
confidence: 77%